2013
DOI: 10.2147/cia.s44245
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen weeks of resistance training can decrease the risk of metabolic syndrome in healthy postmenopausal women

Abstract: BackgroundThe postmenopausal phase has been considered an aggravating factor for developing metabolic syndrome. Notwithstanding, no studies have as yet investigated the effects of resistance training on metabolic syndrome in postmenopausal women. Thus, the purpose of this study was to verify whether resistance training could reduce the risk of metabolic syndrome in postmenopausal women.MethodsTwenty postmenopausal women were randomly assigned to a resistance training protocol (n = 10, 53.40 ± 3.95 years, 64.58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
52
1
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 46 publications
11
52
1
11
Order By: Relevance
“…However, the results do not allow for comparison mainly due to the fact that the present study did not evaluate BP in an acute way. Chronic studies with total training volume (sets + frequency … continues + duration + number of exercises + number of repetitions + load) found responses similar to those of the present study regarding BP [26][27] . In general, protocols of previous studies did not compare different RT frequencies, but adopted training protocols with frequency of two or three weekly sessions.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the results do not allow for comparison mainly due to the fact that the present study did not evaluate BP in an acute way. Chronic studies with total training volume (sets + frequency … continues + duration + number of exercises + number of repetitions + load) found responses similar to those of the present study regarding BP [26][27] . In general, protocols of previous studies did not compare different RT frequencies, but adopted training protocols with frequency of two or three weekly sessions.…”
Section: Discussionsupporting
confidence: 83%
“…The literature presents conflicting results regarding the effect of RT on BP. Previous studies have reported increases 17 , decreases [18][19][20][21][22][23] or did not find [24][25][26][27] changes in rest BP in different training protocols and populations. Divergences of results seem to be related to the characteristics of samples studied, mainly in relation to pre-experiment BP values.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding specific lipoproteins fractions and TG, we observed beneficial changes to both HDL-C and LDL-C as well as to the TG irrespective of training status. Previous studies have also observed positive (Conceicao et al 2013;Maesta et al 2007;Williams et al 2011), conceivably by mediating LDL-C plasma removal, and lipid oxidation via an increase in lipoprotein lipase (Mann et al 2014). RT also can increase the ability of skeletal muscle to use fat, thereby reducing the levels of plasma lipids (Mann et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to its effects on enhancing muscular strength, RT provides numerous additional benefits to older adults' health that may directly impact cardiovascular disease risk, including positive changes in body composition (American College of Sports Medicine 2009; Garber et al 2011), improvements in metabolic profile (Conceicao et al 2013;Kelley and Kelley 2009;Maesta et al 2007;Williams et al 2011), and a reduction in inflammatory markers (de Salles et al 2010;Lera Orsatti et al 2014;Phillips et al 2012;Stewart et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Conceicao et al 46 verificaram os efeitos de 16 semanas de treinamento resistido (3 séries de 8-10 RM e 60-90 segundos de intervalo entre as séries) nos fatores de risco para síndrome metabólica em mulheres na pós menopausa e observaram redução estatisticamente significante do Z-score para síndrome metabólica, glicose de jejum (-13.97%), percentual de gordura corporal (-6.75%), e aumento da massa corporal magra (+2.46%), força muscular de membros inferiores (+41.29%) e membros superiores (+27.23%). Estes estudos demostram que programas de treinamento resistido podem ser um importante componente nos programas de saúde pública, contribuindo para melhoria da saúde e progressão do desenvolvimento de doenças.…”
Section: Treinamento Resistidounclassified